(untitled) (Materiali di Estetica. Terza serie, 2022)
An important contribution by Antonia Pozzi to the journal "Vita Giovanile" (the future "Corrente") is examined here: an essay on Aldous Huxley, centred mainly on Eyeless in Gaza but also referring to the other works of the English writer. Pozzi was particularly attracted by the idea that such a writer with scientific approach like Huxley developed a style closely linked to life. Life understood not only as reason but also as body, emotion, empathy towards others and towards the world. This was in fact the way Pozzi herself conceived life and writing